Legal status disparities in preventive care usage among Latino immigrants in California: A cross-sectional analysis. - Tianjian Lai; Brian Tuohy; Roger Waldinger (PLOS Global Public Health, 2025)
This paper examines disparities in preventive care utilization among Latino immigrants, differentiating between naturalized U.S. citizens, permanent residents, temporary status holders, and undocumented immigrants. We analyzed data from the 2015-2016 California Health Interview Survey (CHIS), a cross-sectional, representative sample of California residents. Our sample consisted of 5,513 respondents who self-identified as foreign-born Latinos. We examined three measures of preventive health: annual checkups, flu vaccinations, and access to mammogram screenings. We applied weighted logistic regression to estimate how immigrants' odds of receiving annual checkups and flu vaccinations in the past year, and mammogram screenings in the past two years, differed by legal status after controlling for various sociodemographic and health factors. We found that naturalized citizens and lawful permanent residents (LPRs) report higher unadjusted odds of having annual checkups (citizen OR = 3.23, p = 0.000; LPR OR = 2.03, p = 0.000), flu vaccines (citizen OR = 2.14, p = 0.000; LPR OR = 1.62, p = 0.000), and mammograms (citizen OR = 3.24, p = 0.000; LPR OR = 1.95, p = 0.005) relative to undocumented immigrants. However, immigrants with temporary legal status do not differ significantly in their rate of preventive care utilization relative to those who are undocumented. This suggests that precarious legal status, rather than outright undocumented status alone, contributes to disparities in preventive care. After controlling for sociodemographic, health status, and health access factors, legal status disparities in flu vaccinations lose statistical significance, while naturalized citizens continue to have higher odds of annual checkups (OR = 1.46, p = 0.032) and mammograms (OR = 2.69, p = 0.000) and permanent residents remain more likely to receive mammograms (OR = 1.68, p = 0.05) relative to undocumented immigrants. Our findings underscore the need to address access to and utilization of preventive care among legally vulnerable immigrants.